Міжнародно-правові стандарти в сфері захисту прав людини та їх вплив на законодавство України - Москалюк, Надія; Слома, Валентина; Mockaliuk, Nadiia; Sloma, Valentyna (ЗУНУ, 2022)
У статті досліджуються міжнародно-правові стандарти у сфері захисту основних прав та свобод людини, особливості їх впливу на Конституцію України та інші нормативно-правові акти. Аналізу підлягає система міжнародних правових актів, яка складається із: Міжнародного білля про права людини, Угод, спрямованих на запобігання та покарання злочинів, що призводять до масових порушень прав людини; Конвенцій, націлених на захист груп населення, які потребують особливого піклування з боку держави; Конвенцій, спрямованих на захист людини від зловживань з боку органів держави та посадових осіб, а також Міждержавних конференцій з прав людини, що приймають заключні документи, обов’язкові для виконання державами-учасницями. The issue of protection of human rights, their observance and proper implementation is an urgent issue nowadays. After all, legislation, ensuring human rights is the main indicator that indicates the sociality, democracy and legal nature of the state. Guarantees of observance and protection of human rights must be enshrined at both the national and international legal levels. In today’s world, ensuring the protection of fundamental human rights has ceased to be the responsibility of an individual country, and has become the main task of the entire international community. Due to the increased attention of the world community to this problem, many declarations, conventions and charters have been adopted by international organizations. International human rights law is generally regarded as international standards, as it is developed on the basis of customary norms, which are formed as a result of the recognition by states of the rules of conduct established by the UN General Assembly in declarations or recommendations. The vast majority of documents, international institutions and protection procedures appeared only in the late 1940s. Human rights standards have contributed to the adoption of a number of universal and regional legal acts in this area. Ukraine is one of the founding members of the United Nations, so it is committed to promoting international cooperation in the field of respect for and observance of human rights and fundamental freedoms. A number of international acts have become the foundation for the Constitution of Ukraine. Thus, Part 5 of Art.55 of the Constitution of Ukraine declares that «everyone is guaranteed the protection of their rights, freedoms and interests from violations and unlawful encroachments by any means not prohibited by law». This corresponds to the principles of the rule of law, which is not limited to the rule of law, but also contains the rules of morality, customs, traditions and so on. The article examines international legal standards in the field of protection of fundamental human rights and freedoms, features of their impact on the Constitution of Ukraine and other regulations.
International legal standards in the field of protection of human rights and their influence on the law of Ukraine
Keywords: захист прав людини; міжнародно-правові стандарти; національне законодавство України про права людини; protection of human rights; international legal standards; national legislation of Ukraine on human rights